Weaving the rururban: an approach to rururbanization processes in the intermediate city of Tunja, Colombia - Bautista Vargas, Andrés Felipe (Universidad Pedagógica y Tecnológica de Colombia, 2023)
At present, the rururban dynamic constitutes profound changes in its forms, expressions and morphologies. It is a new state of the urban in the rural where times, spacesand geographies of diverse nature converge, but where the rural prevails. But how are these processes rewritten? What are these ways of analysis? This document analyses the rururban space of Tunja-Cómbita-Oicatá, an area witness of changes and new configurations exposed in spatial patterns of rurbanization increasingly present in its interstitial areas. for this, a multitemporal analysis of Lansadt 4 (1980), Spot (2000), Landsat 7 (2009) and Google Maps, TIFF format (2019) images were carried out through geographic information system (GIS) tools. As main results, urban occupation processes are identified, in the case of Tunja, higher than 90%, and for the other municipalities of 70 and 40% respectively. This expansion, mostly generated by the city, affects the appearance of a new discontinuous, dispersed, multipolar and diversely located urban fabric and breaks into the local dynamics of these territories and their geographies, challenging their traditional, peasant and agrarian characteristics and installing others.